HRD system in India: conceptual framework, measure development and model fit - Jain, Ravindra; Kamble, Sachin; Premkumar (2013)
The authors suggested a theoretical framework with management concerns and management styles having definite impacts on HRD practices which in turn have positive impacts on productivity and adaptability of human resources. The validity of the four scales developed for the purpose was tested through the confirmatory factor analysis and the scales were found valid. Structural Equation Modeling (SEM) was exercised and the conceptual framework of HRD system was validated. The findings suggest that management professionals should understand that there exists a dire need to improve the level of HR effectiveness in all respects. - Reproduced.
Keywords: Human resource development - India; Human resources development